Case report: A surgically treated case of diaphragmatic clear cell carcinoma without relation to endometriosis. (April 2023) - Moriyasu, Ryo; Mishima, Osamu; Sunakawa, Taiki; Otagiri, Noriaki; Ito, Nobuo; Tauchi, Katsunori
Abstract: Introduction and importance: Diaphragmatic tumor is a rare neoplastic disease. Only three reports have revealed diaphragmatic primary clear cell carcinoma. On the other hand, secondary membranous nephropathy is sometimes triggered by the carcinoma. We describe a case of primary diaphragmatic clear cell carcinoma without relation to endometriosis or ovarian malignancies, and secondary membranous nephropathy was triggered by diaphragmatic primary clear cell carcinoma. Case presentation: A 67-year-old woman was found to have membranous nephropathy due to examination for renal dysfunction. A rare diaphragmatic tumor was identified on CT scan for rule out secondary membranous nephropathy. She had underwent resection of the right diaphragm tumor and reconstruction with expanded polyterafluoroethylene (e-PTFE). Clinical discussion: Pathological examination revealed the presence of clear cells with papillary arrangement and no findings of the endometriosis. Immunohistochemistry revealed that the tumor was positive for CK7, p53, and HNF-1-beta. And there had been no evidence of ovarian malignancies. A diagnosed of clear cell carcinoma of the right diaphragm without relation to endometriosis or ovarian malignancies was made. After resection of the tumor, it was revealed that her renal function was improvement. Conclusion: This is the first report of diaphragmatic clear cell carcinoma without relation to endometriosis or ovarian malignancies that caused secondary membranous nephropathy. One year after the resection of the tumor, she is being followed up and has shown no signs of recurrence. Highlights: This is a surgically treated case of diaphragmatic clear cell carcinoma without relation to endometriosis or ovarian malignancies. The excision site at the diaphragm was reconstructed with expanded polyterafluoroethylene. Secondary membranous nephropathy was triggered by diaphragmatic clear cell carcinoma